Profil guru SMK Teknik Pemesinan dan relevansinya dengan kurikulum Prodi Pendidikan Teknik Mesin FT UNY - Surono Surono; Wagiran Wagiran (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan untuk mengungkapkan: (1) profil ideal guru Sekolah Menengah Kejuruan (SMK) Kompetensi Keahlian Teknik Pemesinan (KKTP), (2) relevansi profil ideal guru SMK-KKTP dengan kurikulum Prodi Pendidikan Teknik Mesin Fakultas Teknik Universitas Negeri Yogyakarta (PTM FT UNY), (3) proses pembelajaran di Prodi PTM FT UNY, dan (4) profil calon guru SMKKKTP. Penelitian ini adalah penelitian kuantitatif dengan metode survei, yang dilakukan di Prodi PTM FT UNY dan sebelas SMK di provinsi DIY. Teknik pengumpulan data yang digunakan adalah dokumentasi dan angket. Teknik analisis data yang digunakan adalah analisis statistik deskriptif. Hasil penelitian adalah sebagai berikut. (1) profil ideal guru SMK-KKTP terdiri dari lima aspek kompetensi yaitu: pedagogik bidang studi keahlian, manajerial, kepribadian, dan sosial. Profil ideal guru SMKKKTP termasuk dalam kategori sangat penting. (2) Pofil ideal guru SMK-KKTP sangat relevan dengan kurikulum Prodi PTM FT UNY. Terdapat 59 kompetensi tambahan dalam kurikulum Prodi PTM FT UNY untuk menyiapkan lulusannya agar dapat bekerja di industri, menjadi instruktur, atau menjadi widyaiswara. (3) Pembelajaran di Prodi PTM FT UNY menurut persepsi dosen termasuk dalam kategori sangat memadai dan menurut persepsi mahasiswa termasuk dalam kategori memadai. (4) Profil calon guru SMK-KKTP menurut persepsi guru pembimbing PPL termasuk dalam kategori baik; menurut persepsi dosen termasuk dalam kategori baik; dan menurut persepsi mahasiswa termasuk dalam kategori baik. THE PROFILE OF VOCATIONAL HIGH SCHOOL TEACHERS OF THE MACHINING ENGINEERING AND ITS RELEVANCE TO THE CURRICULUM OF MECHANICAL ENGINEERING EDUCATION STUDY PROGRAM, FACULTY OF ENGINEERING, YOGYAKARTA STATE UNIVERSITYAbstractThis study aims to reveal: (1) the ideal profile of vocational high school teachers of the expertise competency of machining engineering (VET teachers of KKTP); (2) the relevance between the ideal profile of VET teachers of KKTP with the curriculum of Prodi PTM FT UNY; (3) the teaching process in Prodi PTM FT UNY; and (4) the profile of the candidates of VET teachers of KKTP. This research was quantitative research with the survey method, conducted at Prodi PTM FT UNY and eleven vocational high schools in DIY province. The data collection techniques used were documentation and questionnaires. The data analysis technique used was the descriptive statistical analysis. The result of this study is as follows. (1) The ideal profile of VET teachers of KKTP consists of five aspects competencies are: pedagogical, subject areas of expertise, managerial, personal, and social. The ideal profile of VET teachers of KKTP is in the very important category. (2) The ideal profile of VET teachers of KKTP very relevant with the curriculum of Prodi PTM FT UNY. There are 59 additional competencies in the curriculum of Prodi PTM FT UNY to prepare graduates to work in the industry, become an instructor, or become trainers. (3) The teaching process at Prodi PTM FT UNY according to the perception of lecturers is in the very adequate category and according to the perception of the students it is in the adequate category. (4) The profile of the candidates of VET teachers of KKTP according to the perception of the supervising teachers of PPL is in the good category; according to the perception of lecturers, it is in the good category; and according to the perception of students, it is in the good category.